Optimal Reliability Allocation Using the Harmony Search Algorithm (HSA) for Component-Level Cost and Reliability Analysis in Complex Systems (Journal of the College of Basic Education, 2026)
In this research, the reliability function of a complex system was calculated, identifying the optimal reliability distribution among the system's components. Most recent studies rely on increasing closed-form functions to relate cost to reliability, knowing that the cost of a component increases as its reliability increases. However, these functions can sometimes be ill-defined or difficult to generate. In this research, MATLAB was used to extract the system's reliability function, and the relationship between cost and reliability across separate datasets was discussed. The reliability and cost of each component were calculated individually using the Harmonic Search Algorithm (HSA), in addition to calculating the total cost and reliability of the system. An exponential feasibility factor cost function was applied within this algorithm to improve performance and achieve the optimal reliability distribution.